Management using the Six Sigma approach to cost rationalization of activities : Application in the Iraqi mechanical carpet factory (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The textile industries play a prominent role in reviving the national economy, but they are currently suffering from several problems, including the high costs of their activities, the low quality of their production processes, and accordingly, the hexagonal diffraction approach came to help analyze production activities to determine which of them are the most expensive and do not have a benefit or cost greater than Its benefit as a result of waste and losses that accompany its implementation. And by applying to the Iraqi mechanical carpet factory, the research reached several conclusions, the most important of which is the presence of several sources of waste and loss, such as activities and operations that do not add value, which affected the increase in costs, as well as the failure of the laboratory to use the tools of strategic cost management in improving the quality of operations and identifying the root problems of rising costs and eliminating sources Wastage of resources and low level of production quality.